2008
DOI: 10.1371/journal.pbio.0060034
|View full text |Cite|
|
Sign up to set email alerts
|

Caldendrin–Jacob: A Protein Liaison That Couples NMDA Receptor Signalling to the Nucleus

Abstract: NMDA (N-methyl-D-aspartate) receptors and calcium can exert multiple and very divergent effects within neuronal cells, thereby impacting opposing occurrences such as synaptic plasticity and neuronal degeneration. The neuronal Ca2+ sensor Caldendrin is a postsynaptic density component with high similarity to calmodulin. Jacob, a recently identified Caldendrin binding partner, is a novel protein abundantly expressed in limbic brain and cerebral cortex. Strictly depending upon activation of NMDA-type glutamate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
288
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(301 citation statements)
references
References 67 publications
13
288
0
Order By: Relevance
“…Consistent with this possibility, a recent study identified Jacob, a caldendrin binding partner, as a synaptically localized cargo of importin ␣1 that translocates to the nucleus after extrasynaptic NMDA receptor activation (10). In the present study, we show that the transcriptional repressor CREB2 is a synaptically localized cargo of importins.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with this possibility, a recent study identified Jacob, a caldendrin binding partner, as a synaptically localized cargo of importin ␣1 that translocates to the nucleus after extrasynaptic NMDA receptor activation (10). In the present study, we show that the transcriptional repressor CREB2 is a synaptically localized cargo of importins.…”
Section: Discussionsupporting
confidence: 91%
“…A slower, more persistent mechanism of signaling to the nucleus involves the transport of soluble molecules from stimulated synapses to the nucleus (6,7). Recent studies have indicated that this type of transport may involve the active nuclear import pathway (8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic NMDAR mediated synpatodendritic [Ca 2þ ] i elevation induces caldendrin binding to Jacob, inhibiting nuclear trafficking and maintaining dendritic organization. This interaction represents a novel mechanism of synapse to nucleus communication and highlights the important roles of CaBP family members in the mammalian central nervous system (Dieterich et al 2008).…”
Section: Calcium Sensor Proteins In Neuronal Functionmentioning
confidence: 86%
“…Particularly signaling from N-methyl-D-aspartate (NMDA) 3 type glutamate receptors to the nucleus has been implicated in synaptic plasticity, and some molecules have been identified that can translocate from synaptic and extrasynaptic sites to neuronal nuclei after NMDA receptor activation (3)(4)(5)(6)(7). In a recent study, we have identified Jacob, a protein that triggers long lasting changes in the cytoarchitecture of dendrites and the number of spine synapses in pyramidal neurons via coupling of NMDA receptor signaling to nuclear gene expression (6). Following activation of synaptic and extrasynaptic NMDA receptors, Jacob is recruited to neuronal nuclei, and this in turn results in a rapid stripping of synaptic contacts and in a drastically altered morphology of the dendritic tree (6).…”
mentioning
confidence: 99%